THE PHENOMENON OF ‘IGBA OSO-AHIA’ IN IGBO ENTREPRENEURSHIP IN A MODERN INDUSTRIAL SOCIETY - Onyemachukwu Umeh, Vincent (African Journal of Social and Behavioural Sciences, 2024)
Evidences have proven that even the existential challenges the Igbo faced such as the Civil War could not deter them from known entrepreneurial spirit and excelling in entrepreneurship and this is palpable in every economic activity they have engaged and engaging in. Rather one of the innovations brought into the marketplace, a practice known in local parlance as igba oso-ahia, is the reason the entire group have come under serious opprobrium. This paper thus x-rayed the activities of Igbo traders in the typical marketplace in order to improve market exchanges and reposition the group. It adopted the ethical value system and community service approach made popular by Shapero and Sokol (1982), and others; and interviewed some randomly selected Igbo traders and elicited the opinions of some enlightened Nigerians in major markets in Abuja, Lagos and Port-Harcourt. At the end, it found that while it may have been a coping method to survive the post-civil war times and the anti-people policies of successive administrations in Nigeria, and even the outright marginalization of the group, the practice is presently odious and attracts serious resentment of the Igbo. It is not only hurting market exchanges and the economy but also the reputation of the group in a highly diverse and complex nation. More still, if the practice is considered tolerable in earlier times, it is out-rightly anachronistic and an anathema in modern industrial society. It therefore calls on Igbo traditional institutions, town unions, and others, for total jettisoning of the unwholesome practice. In addition, government and market authorities should ensure that right compliances are maintained in the marketplace.